Diversity of Seagrass in Sire Beach, West Nusa Tenggara - Nurbayanti, Elya Sri; Naura, Diah Ayu; Aprilliyanti, Dini Aziza; Ismayani, Ismayani; Adhawati, Laela; Auliya, Lana; Apriliani, Lilik Ayu; Prayoghi, M. Satrio; Arizmayadi, M. Yusran; Chandri, Dining Aidil; Ghazali, Mursal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Seagrass ecosystems are vital for marine biodiversity, carbon storage, and coastal protection but face threats from human activities and environmental changes. This study examines seagrass diversity, distribution, and ecological conditions at Sire Beach, North Lombok Regency, West Nusa Tenggara. Research conducted from October to December 2024 used transect-quadrat and exploratory methods at three stations. In addition to biotic elements like seagrass species, abiotic variables including temperature, pH, salinity, and dissolved oxygen were simultaneously examined. Eight seagrass species were identified: Halodule pinifolia, Cymodocea serrulata, Syringodium isoetifolium, Cymodocea rotundata, Thalassia hemprichii, Halophila ovalis, Enhalus acoroides, and Halodule uninervis. Enhalus acoroides dominated due to its adaptability and robust root systems. Diversity (H’=1.66), dominance (0.499), and evenness (0.798) indices indicate moderate biodiversity and balanced species distribution. Abiotic factors, including temperature (29–30.5°C) and pH (7.14–7.60), were optimal, though nutrient levels (phosphate 0.10–0.15 mg/L, ammonia 0.02–0.03 mg/L) could affect photosynthesis. Sire Beach's seagrass ecosystem is moderately diverse and stable but affected by anthropogenic pressures. Conservation measures and long-term monitoring are recommended to sustain this critical habitat.